Planting and Annual Cultural Maintenance Costs for Reset-Replacement Trees in a Florida Citrus Grove in 2016: FE995/FE995, 7/2016 - Burani-Arouca, Marina; Futch, Stephen H.; Singerman, Ariel (EDIS, 2016)
Replacement of diseased, unproductive or dead trees is an important part of the cultural program for citrus groves. This 5-page fact sheet uses prices and productivity rates collected through a telephone survey in May 2016 to analyze the different preferred management and reset practices. Written by Marina Burani-Arouca, Stephen H. Futch, and Ariel Singerman, and published by the Food and Resource Economics Department, July 2016. FE995/FE995: Planting and Annual Cultural Maintenance Costs for Reset-Replacement Trees in a Florida Citrus Grove in 2016 (ufl.edu)